Confabulations - Jugo, Celeste Aida Abad (2009)
In this dissertation, the writer explores jackdaw and dog metaphors to help represent her reading and writing life as well as her theory of writing. The dissertation essay begins with an aerial view of her interest in stories, the inspirations that feed her and her writing (whether these be inspirations of a highly artistic or highly questionable nature), the thieving from greater minds in order to write and explore possibilities, and the disguise that is afforded her in the form of fiction; after which the essay proceeds with dog imagery. Dogs are nearer the earth and can study and sniff out things more minutely; they provide for the writer an interesting and useful trope for writing; one could dig up stuff from history or memory or the imagination, one could chase one's tale (spelled T-A-L-E), and one could follow a trail to see where the story leads. The dissertation essay discusses the writer's concerns spanning a ten-year period: the portrayal of young characters; the attempts at closure and "organic unity"; the tiny experiments in point of view, structure, language, setting, and epiphany; and the shift from the realist mode to a more speculative approach. The essay is followed by an assorted collection of short fiction. Taking one's cue from Nadine Gordimer who says "the rational is simply another, the most obvious, kind of fantasy. Writers turn to the less obvious fantasy as a wider lens on ultimate reality" (265), the collection could be viewed on a spectrum called "Fantasy," from the most obvious kind of fantasy, which attempts verisimilitude, to the least obvious, which completely takes the reader out of this world and puts her in another.
The essay -- Confabulations -- Introduction : seven ways of looking at a jackdaw -- Part I. Doggone reality -- Part II. Dog tales -- Part III. Dog dreams -- Part IV. Dog myths -- Afterword/After-world : the stuff of stars and Doggy Doo -- Works cited -- The stories -- Saints and souls -- The skylab -- The grand jeté -- A Cinderella soap -- The patient -- Bruno butter -- Sweet summer -- Kapayapaan lobby -- Ikot jeep -- Massage -- The abominable snowman -- Jan's door -- Green girl -- The confessional -- Honor among thieves -- High noon -- Dragon brother.
"October 2009."
Thesis (Ph.D. English Studies : Creative Writing)--University of the Philippines Diliman.
Keywords: Short stories, Philippine (English).; Philippine essays (English).; Domestic animals in literature